ADU NARASI KORBAN DAN POLISI DALAM TRAGEDI KANJURUHAN - Prasetya, Denny (Master of Communication Science Program, Universitas Diponegoro, 2024)
This study aims to analyze the narrative between the victims and the police on the tragedy that occurred at the Kanjuruhan Stadium, Malang, East Java. This study uses the main analytical tool that originates from the Narrative Paradigm theory initiated by Walter Fisher. The research method used is a qualitative method with narrative analysis technique. The object of analysis in this study is the narratives of the victims taken from several programs that invite them as speakers, and the narratives from the police’s side taken from the video uploaded in the police’s official Twitter account and the results of a press conference from the police. The results of the study found that there was a conflicting narrative between the victim and the police. The narrative developed by the victim has fulfilled the principles of coherence and fidelity so that it is more trusted by the community, and on the other side, the narrative from the police has received less trust from the community.